Digital Systems in Tourism Management and International Practices: A Comparative Perspective with Uzbekistan - Makhmudjonovna, Radjapova Nasiba; Nuralievich, Sultan Najmiddinov (SABA: Journal of Tourism Research, 2025)
This article explores the digital transformation of tourism management, emphasizing international best practices and their relevance for Uzbekistan. It reviews the adoption of digital systems—such as AI, Big Data, VR/AR, CRM, ERP, and IoT—in tourism across countries like Singapore, the UAE, Spain, and Estonia. The study highlights Uzbekistan’s ongoing digital initiatives in tourism, identifies challenges in integration and infrastructure, and recommends steps toward building a sustainable, tech-driven tourism industry. The paper offers comparative insights and actionable strategies for leveraging digital tools to enhance tourism competitiveness, safety, and service quality.